Canadian Immigration Policies: Securing a Security Paradigm? - Antonius, Rachad; Labelle, Micheline; Rocher, François (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
Security is increasingly becoming a main concern in Canadian society. Post 9/11, the challenge for Canada is to strike a balance between maintaining the flow of immigration necessary for its demographic and economic development and projecting an image of openness at a time when security measures are globally being strengthened. In the post-9/11 context, it is important to assess the extent to which security concerns have infiltrated policy discourse and choices to evaluate whether these concerns are changing the overall objectives and goals pursued by the Canadian government through policy realms such as immigration. We argue that the security logic has become embedded since 9/11. Although security concerns were becoming increasingly prevalent through the 1990s, the post-9/11 period has allowed the security agenda to prevail over the human rights agenda and concerns for civil liberties. The emphasis on criminal law to address terrorism and the use of immigration policy to impose security measures is a step away from upholding goals of social justice, equality, and openness that are still central to its policies. The paper addresses these concerns and examines options to allow human rights and citizenship rights concerns to prevail.